Modelling energy consumption of electric freight vehicles in urban pickup/delivery operations: analysis and estimation on a real-world dataset. (December 2018) - Fiori, Chiara; Marzano, Vittorio
Highlights: Development of an energy consumption model for Electric Freight Vehicles. Real-world data collection during pickup/delivery operations of EFVs in Rome. Calibration and validation of the energy consumption of EFVs using real-world data. Impact evaluation of the instantaneous weight on-board on the energy consumption. Flexible and reliable modeling of the energy consumption for an EFV fleet. Abstract: Electric Freight Vehicles (EFVs) are a promising and increasingly popular alternative to conventional trucks in urban pickup/delivery operations. A key concerned research topic is to develop trip-based Tank-to-Wheel (TTW) analyses/models for EFVs energy consumption: notably, there are just a few studies in this area. Leveraging an earlier research on passenger electric vehicles, this paper aims at filling this gap by proposing a microscopic backward highly-resolved power-based EFVs energy consumption model (EFVs-ECM). The model is estimated and validated against real-world data, collected on a fleet of five EFVs in the city centre of Rome, for a total of 144 observed trips between subsequent pickup/delivery stops. Different model specifications are tested and contrasted, with promising results, in line with previous findings on electric passenger vehicles.